Aluminium chip waste for secondary materials using direct recycling process - Maizatul Mastura, Muhammad Nazri (2013)
Direct recycling process is a simple method because it only consumed a small amount of energy and no harmful effect on the environment compare to the conventional recycling process in which involved re-melting the chips to produces secondary materials, the aims of this project is to investigate the influence on different shape and size of AA6061 and AA7075 chips as secondary materials billet using cold compaction process. Different type of chip was cut by various turning parameter on CNC turning machine. Turning chips from aluminium alloys were cold compacted in a closed cylindrical die by means of Universal Testing Machine (UTM). Several pre-compacting are needed due to low filling density of chip inside the die cavity at once. The compacted billets are analyzed base on their density, porosity percentage and structure by using manual calculation. Results show that the different shape and size of the chips influence the final compacted billets integrity. Smaller the thickness of the chip, the higher the resulting density after the compaction process in which increasing the number of compacting for each operation leading to differences in the volume. The lower the relative density percentage shows the poor quality of their solidification. At the same time, the higher the thickness of the chip, the higher the percentage of the resulting porosity and more empty space formed between the compressed chip's structures. As a conclusion, the depth of cut plays an important role in producing the desired chip thickness where the spindle speed and feed rate lead to the length of the chips. Furthermore, the chip's thickness influenced the density of compacted billets and they have different volume due to differ number of compacting. The number of compacting for each type of chips affected the density of the compacted billets where the relative density shows the quality of the compacted specimens. Last but not least, the porosity percentage shows the empty space between the chips occur on the structure of the compacted billets.